DESAIN AYUNAN BAYI DARI IKM KERAJINAN ROTAN MENGGUNAKAN METODE QUALITY FUNCTION DEPLOYMENT - Febriza Imansuri; Irma Agustiningsih Imdam; Indra Yusuf Rangkuti; Fredy Sumasto; Dewi Auditiya Marizka (Politeknik Negeri Batam, 2026)
Currently, Small and Medium Enterprises (SMEs) are required to meet consumer needs by developing innovative products to compete in the market. Based on interviews with customers of rattan handicraft products, baby swings receive the most complaints, particularly regarding safety, comfort, and durability. Therefore, this study focuses on redesigning rattan baby swings to align with customer needs and compete with modern household products. To achieve this, the study identifies the design requirements and technical characteristics desired by customers through data collection, Quality Function Deployment (QFD) Phases 1 and 2, and product design development. The results of Phase 1 QFD indicate that customer design needs encompass economic, ergonomic, durability, aesthetic, and feature aspects. Meanwhile, the results of Phase 2 QFD indicate that the technical characteristics manufacturers must meet include the use of anthropometric data, design modifications, selection of high-quality raw materials, attractive colors, comfortable padding, and materials free from hazardous chemicals. The swing dimensions were determined based on anthropometric data for adults and infants, referencing the 50th percentile of adult hip height and the 95th percentile of infant arm reach and span.